(untitled) - Cherlin, Andrew J. (New York, 1996)
Written by one of the leading authorities in the field. Public and Private Families examines the family through two lenses, the familiar private family in which we live most of our lives and the public family where we as adults deal with broader societal issues such as the care of the elderly, the increase in divorce, and childbearing outside of marriage. thus the books looks at both intimate personal concerns. such as whether to marry and societal concerns such as government policies that affect families.
Keywords: Family,Gia đình; United States,Hoa Kỳ